ICA-CEPA Within the Framework of GATT 1994: Negative Impact on Indonesia as a Developing Country - Lasma Ria Siregar; Roida Nababan; Sovia Simamora (Journal of Law, Politic and Humanities, 2026)
The Indonesia-Canada Comprehensive Economic Partnership Agreement (ICA-CEPA) is a comprehensive trade agreement that stands under the framework of the GATT 1994, specifically Article XXIV, which regulates the establishment of free trade areas and customs unions. The purpose of this article is to examine Indonesia's position in the ICA-CEPA negotiations from the perspective of international trade law and assess whether the provisions of the GATT provide sufficient space for Indonesia to protect its national interests. This study uses a normative-critical approach with an analysis of international laws and agreements, as well as a policy review related to the mechanism of revocation and postponement of agreements. The results of the analysis show that the GATT 1994, in particular Article XXIV, only provides a legal basis for the establishment of the ICA-CEPA, but does not clearly regulate the clause for the revocation or postponement of the implementation of the agreement. These provisions are entirely dependent on the text of the ICA-CEPA itself, so Indonesia has limited power to terminate or suspend the agreement if it is proven to have a severe negative impact on the economy and the sovereignty of domestic regulations. This article argues that the absence of a strong legal basis in the 1994 GATT makes the ICA-CEPA potentially serve more as a trade political tool that benefits Canada, while Indonesia is in a less protected position within the structure of the agreement.